The Rate of Convergence of Lupas q-Analogue of the Bernstein Operators - Heping Wang; Yanbo Zhang (Abstract and Applied Analysis)
We discuss the rate of convergence of the Lupas q-analogues of the Bernstein operators Rn,q(f;x) which were given by Lupas in 1987. We obtain the estimates for the rate of convergence of Rn,q(f) by the modulus of continuity of f, and show that the estimates are sharp in the sense of order for Lipschitz continuous functions.